2020
DOI: 10.1177/0022057420944843
|View full text |Cite
|
Sign up to set email alerts
|

A Close-Up on a Predictive Moment: Illusion of Knowing or Lack of Confidence in Self-Assessment?

Abstract: Prediction allows learners to adjust behavior toward the future by exploiting information pertaining to the present and the past. Through a field study, we examined whether poor performing students are truly unaware of not knowing their deficiencies as the illusion of knowing (IoK) phenomenon implies. College students’ ability to predict their final test performance was surveyed as a function of experience (before and after the test), performance level, and self-efficacy. In this study, high performers’ prospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 27 publications
4
9
0
Order By: Relevance
“…Second, recent evidence has questioned the conventional interpretation of the effect. For instance, although students from different parts of the world tend to conform to the pattern of estimations that defines the Dunning–Kruger effect, poor performers may also be less confident in their test predictions than higher performers [ 8 , 9 , 10 , 11 ]. Poor performers may also exhibit less self-efficacy (i.e., overall confidence in their abilities) than students performing well [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, recent evidence has questioned the conventional interpretation of the effect. For instance, although students from different parts of the world tend to conform to the pattern of estimations that defines the Dunning–Kruger effect, poor performers may also be less confident in their test predictions than higher performers [ 8 , 9 , 10 , 11 ]. Poor performers may also exhibit less self-efficacy (i.e., overall confidence in their abilities) than students performing well [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, although students from different parts of the world tend to conform to the pattern of estimations that defines the Dunning–Kruger effect, poor performers may also be less confident in their test predictions than higher performers [ 8 , 9 , 10 , 11 ]. Poor performers may also exhibit less self-efficacy (i.e., overall confidence in their abilities) than students performing well [ 11 ]. Taken together, these findings have been interpreted as suggesting that poor performers face a serious dilemma when thinking about their performance on a test.…”
Section: Introductionmentioning
confidence: 99%
“…To wit, if self-efficacy is conceptualized as a motivational trait [42] linked to learners' engagement/motivation [43,44], it is expected to translate into actions (e.g., completion rates, dedication, commitment, goal-setting, etc.) conducive to academic accomplishments in specific tasks as well as overall [45][46][47][48][49][50][51][52]. However, evidence also exists either of an inverse relationship between self-efficacy and educational success (when self-efficacy becomes over-confidence) or of no relationship at all [53][54][55].…”
Section: Discussionmentioning
confidence: 99%
“…Yet, in the extant literature, evidence of a link between self-efficacy and performance, prediction accuracy, or subjective confidence is mixed. For instance, Al Kuhayli et al (2019) found no evidence of a link between self-efficacy and either class performance or metacognition, whereas Pilotti et al (2020) reported low self-efficacy to be associated with poor performance.…”
Section: Literature Reviewmentioning
confidence: 99%